2017
DOI: 10.1159/000479517
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Poor Academic Performance with Tic Disorders: A Longitudinal, Mainstream School-Based Population Study

Abstract: Background: Little is known about the academic performance of students with tic disorders (TD). Our aim was to investigate the association of TD and poor academic performance over time. Methods: Longitudinal, observational study of mainstream schoolchildren comparing grade retention (GR) and learning disorders (LD) in students with vs. without TD between 2010 and 2014. Students with vs. without TD based on DSM-IV-TR criteria, or with vs. without GR and LD were compared in terms of comorbidities, school, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…It is frequently associated with comorbidities such as Attention Deficit Hyperactivity Disorder (ADHD) and Obsessive Compulsive Disorder (OCD; Abramovitch et al, 2015). Additionally, social and emotional difficulties (Cutler et al, 2009), impaired school functioning (Cubo et al, 2017) behavioural difficulties and a diminished quality of life (Eapen et al, 2016) are also frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently associated with comorbidities such as Attention Deficit Hyperactivity Disorder (ADHD) and Obsessive Compulsive Disorder (OCD; Abramovitch et al, 2015). Additionally, social and emotional difficulties (Cutler et al, 2009), impaired school functioning (Cubo et al, 2017) behavioural difficulties and a diminished quality of life (Eapen et al, 2016) are also frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Les tics semblent influencer négativement la performance scolaire des élèves qui présentent un SGT (Abwender et al, 1996;Comings et Comings, 1987;Conelea et al, 2011;Cubo et al, 2013Cubo et al, , 2017Dooley, Brna et Gordon, 1999;Gorman et al, 2010;Happich, 2012;Leckman et al, 1998;Packer, 2005;Wilson et Shrimpton, 2003). Certains élèves qui présentent un SGT rapportent qu'ils remarquent une lenteur d'apprentissage, lorsqu'ils se comparent à leurs camarades de classe (De Lange, 2000;Rivera-Navarro et al, 2014;Smith et al, 2015).…”
Section: Difficultés D'apprentissageunclassified
“…Children's tic disorder is a common movement disorder in childhood, and its incidence has gradually increased in recent years (Knight et al, 2012;Cubo et al, 2017). Its prevalence rate among preschool children has reached as high as 6.1% , with a male-to-female ratio of about 4:1 (Robertson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%